Phase Transformations and Dislocations Mechanisms of Al0.3CoCrFeNi High Entropy Alloy: A Nanoscale Investigation - Dheyaa F. Kadhim (Genius Journals, 2023)
In the present investigation, the change of phase transition, the mechanism of dislocation, and the mechanical characteristics of the Al0.3CoCrFeNi high-entropy alloy was examined using molecular dynamics simulations. The affecting variables, such as temperature and strain rate, have been taken into account. The findings reveal that the phase transitions from the original single face-centered cubic form to hexagonal closepacked, body-centered cubic and amorphous phase as the strain develops. In particular, this change happens following the yield strain. Al0.3CoCrFeNi HEA's compressive characteristics are negatively impacted by temperature rise. The shear strain advances as the temperature raises and is distributed uniformly while the dislocation density decrease. In contrast, the yield stresses of high-entropy alloys climb noticeably when the strain rate rises. With rising temperatures, the dislocation density rises. Additionally, the process of phase change is critical for stacking defects. The findings offer a fundamental insight of plastic deformation in Al0.3CoCrFeNi HEA and are qualitatively compatible with experiments.
Keywords: Al0.3CoCrFeNi High-Entropy Alloys; Multi-component Alloys; Molecular Dynamics Simulation